IMPLEMENTASI PASAL 11 AYAT (1) UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA : PERSPEKTIF PERJANJIAN KREDIT DENGAN JAMINAN FIDUSIA PADA PERUSAHAAN PERSEROAN PEGADAIAN - Tirtawati, Ni Wayan; Atmadja, I Dewa Gde; Wijaatmadja, Gde Marhendra (Acta Comitas; Vol 1 No 2 (2016)DO - 10.24843/AC.2016.v01.i02.p15, 2016)
Pawnshop Company is a State Owned Enterprises ( SOEs), which is engaged in the business of providing credit services and applicable statutory lien for anyone with a moving objects collateral requirement . In order to develop the business, so Government Regulation No. 103 of 2000 was issued , stated of the granting of the loan based on the collateral of fiduciary money . As an institution that provides credit to guarantee the fiduciary shall comply with the provisions set out in Law No. 42 of 1999 , especially Article 11, paragraph ( 1) which states that the objects are burdened with fiduciary collateral required to be registered , but in reality there is no Pawnshop Company comply with Article 11 paragraph ( 1) of Law No. 42 of 1999 on Fiduciary . Based on the gap das sein and das sollen , then can be formulated the problem of how fiduciary guarantee enrollment application pursuant to Article 11 paragraph ( 1) of Law No. 42 of 1999 on Company Pawnshop and how execution of fiduciary insurance company that is not registered by the Company Pawnshop when borrowers are in default. Empirical legal research is used in this thesis , because it’s getting out of the gap between das Sein and das sollen . The approach used in this thesis is the legislation approach , case-based approach , and the analytical approach . The nature of the research in this study was a descriptive study, sites in the Pawnshop Company branch Denpasar and Tabanan . The data used in this thesis is the primary data / field data and secondary data / literature . Data collecting techniques used in this thesis is planned interview techniques and reading literature . Sampling techniques used in this thesis is purposive sampling and the data obtained are presented in descriptive qualitative . The results of this problem study is application of fiduciary guarantee enrollment on the Pawnshops Company, that disobedience to law number 42 of 1999 Article 11 paragraph (1) was happened, while the execution of fiduciary insurance company that is not registered by Pawnshop Company if debtor in default is done by a family way.
Keywords: Registration, Credit, fiduciary, breach of contract, execution